Evaluating the Effects of Trade on Militarized Behavior in the Context of Territorial Threat. Issue 1 (21st April 2016) - Lee, Hoon; Rider, Toby J.
Abstract: Does trade reduce conflict even when states compete over high-salience issues (e.g., territory)? Despite recent challenges to liberal peace theory, few studies have examined whether the trade-reduces-conflict argument is robust to particularly conflict prone issues like territory. We evaluate whether trade reduces not only violent conflict over territory, but also the incentives to use specific power politics behaviors (e.g., arms races) associated both with territorial competition and a higher probability of war. As key causal mechanisms, we rely on opportunity costs and the ability to credibly signal information that increased trade generates, reducing states' incentives to engage in violent conflict and arms races. Empirical analyses, using multiple sample populations and different measures of key indicators and outcomes, are consistent with our expectations. The results suggest that trade may reduce conflict both directly, by decreasing the likelihood of militarized disputes, and indirectly, by reducing the likelihood of power politics strategies like arms races, thought to increase the likelihood of war.